Pemimpinan Profesional yang Mengembangkan Budaya Sekolah - Annisa Anggraini; Mifta Norjanah; Nabila Fahmi Romli; Nawang Wulan Ramadhani; Celia Cinantya; Aslamiah Aslamiah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
A professional leader of an educational institution is someone who is able to provide direction, set goals to be achieved, provide solutions to every problem, make various decisions, planning and strategies. He is a great person in implementing concepts. He actively communicates, coordinates, supervises and conducts evaluations. The most important thing is that he motivates teachers and education personnel to become professional teachers and education personnel. He builds morale and a spirit of togetherness in the madrasah educational institution, teaches, trains, and gives advice. All of these hopes will be realized if a leader has the integrity to lead the madrasah educational institution to become an excellent and quality institution. Leader, which means